Effect of interleukins response to ECM-induced acquisition of drug resistance in MCF-7 cells - Ohbayashi, M.; Yasuda, M.; Kawakami, I.; Kohyama, N.; Kobayashi, Y.; Yamamoto, T. (Experimental Oncology, 2008)
Aim: To examine the effect of various components of extracellular matrix (ECM) on acquisition of drug resistance to taxol and camptothecin by breast carcinoma cell line MCF-7. Methods: Cancer cells were cultured on bovine serum albumin (BSA), vitronectin (VN), fibronectin (FN), collagen type I (COL-I), or Matrigel-coated plates with or without taxol (paclitaxel) or camptothecin treatment. The effect of anticancer drugs on cell growth was accessed by XTT assay, and the alterations of cellular morphology were examined by phase contrast microscopy. Immunofluorescence study was performed using monoclonal anti-b-tubulin antibody. Results: All cell lines showed a significant decrease in cell survival when treated with anticancer drugs without components of ECM, whereas survival rates of Caco-2, MCF-7 and NCI-H292 were significantly increased when cells were cultured on COL-I- and Matrigel-coated dishes after treatment with paclitaxel or camptothecin. MCF-7 cells showed and maintained a colony formation when cultured on the COL-I- and Matrigel-coated dish. Moreover, cytotoxicity (IC50) was decreased by taxol (paclitaxel) or camptothecin treatment during colony formation in MCF-7 cells, suggesting that morphological changes could increase survival of cells treated with anticancer drugs. Thick circumferential bundles of microtubules around the periphery of the cells and chromatin condensation was not observed for MCF-7 cells on COL-I- and Matrigel-coated dishes treated with paclitaxel. To confirm this, spheroid cells were prepared, and we found that cytotoxicity was decreased for these cells, and significantly increased when cells were co-cultured on Matrigel- or COL-I-coated upper wells. The effect of anticancer drugs on cell survival was efficiently inhibited by interleukin-6 (IL-6) and interleukin-8 (IL-8). Conclusions: Present results suggested that not only integrin-ECM interactions but also other factors such as IL-6 and IL-8 secreted by cancer cells, cultured on COL-I and Matrigel dishes, are involved in the acquisition of drug resistance by MCF-7. Цель: изучить влияние различных компонентов внеклеточного матрикса (ECM) на приобретение химиорезистентности
к таксолу и камптотецину клетками линии карциномы молочной железы MCF-7. Методы: клетки культивировали на платах,
покрытых бычьим сывороточным альбумином (BSA), витронектином (VN), фибронектином (FN), коллагеном I типа (COL-I)
или матригелем, без и с добавлением таксола (паклитаксел) или камптотецина. Влияние противоопухолевых препаратов на
рост клеток изучали с помощью XTT-теста, изменения клеточной морфологии отмечали в фазовом контрастном микроскопе.
Иммунофлуоресцентным методом определяли экспрессию β-тубулина. Результаты: для всех клеточных линий показано
существенное снижение выживаемости после культивирования с противоопухолевыми препаратами без компонентов ECM, в то
время как уровень выживаемости клеток Caco-2, MCF-7 и NCI-H292 значительно возрос при культивировании с таксолом или
камптотецином в чашках, покрытых COL-I и матригелем. Для клеток MCF-7 показано формирование и сохранение колоний при
культивировании в чашках с COL-I и матригелем. Более того, цитотоксичность (IC50) таксола и во время колониеобразования
клеток MCF-7 была снижена, что позволяет предположить, что морфологические изменения могут влиять на выживаемость
клеток при культивировании с химиопрепаратом. Для клеток MCF-7, выращиваемых на чашках с COL-I и матригелем, не
отмечали образования плотных периферических узлов микротрубочек и конденсации хроматина. Для подтверждения данного
наблюдения проведены опыты с клетками, растущими в виде сфероидов. Показано, что цитотоксичность химиопрепаратов по
отношению к этим клеткам снижалась и значительно повышалась при ко-культивировании с матригелем или COL-I в верхних
камерах. Снижение выживаемости клеток под действием химиопрепаратов эффективно ингибировалось интерлейкином-6
(IL-6) и интерлейкином-8 (IL-8). Выводы: настоящие исследования показали, что не только интегрин-ECM-взаимодействия,
но также и другие факторы, такие как IL-6 и IL-8, секретируемые опухолевыми клетками на чашках с COL-I и матригелем,
участвуют в приобретении химиорезистентности опухолевыми клетками MCF-7.